Aplikasi Kamus Bahasa Indonesia – Palembang Menggunakan Algoritma Interpolation Search Berbasis Android - Yohan Syafri; RM. Nasrul Halim (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
A dictionary is a book that has been arranged in alphabetical order, the dictionary that we usually find is complete and good, but lately the use of book dictionaries has become a bit behind because people prefer an easy way to interpret a word, namely using an electronic dictionary. Nowadays, there are many Palembang language dictionary applications based on android, but this application has not changed too much from other similar applications. The author took the initiative to develop this electronic dictionary application so that it looks more attractive and user friendly, this application can later facilitate the communication process between tourists and the people of Palembang City, and can be a place to preserve the Palembang language. In the process of making this mobile application, the author uses an interpolation search algorithm to make it easier to search for sorted data tables or files that have a scalar key. Data collection techniques that will be used by conducting observations, interviews and using the Mobile-D development method. The result of this research is an android-based Indonesian-Palembang and Palembang-Indonesian translator dictionary application.